Natur Antropologi: Memahami Keragaman Potensi Humanitas Dalam Konteks Komparatif Dengan Perspektif Kristen - Stenly R. Paparang (JURNAL LUXNOS, 2018)
Abstract: This article looks at the anthropology of how humans understand and assess the ins and outs of life, and draws conclusions to be used as a guide for life in shaping moral, spiritual, comfort, peace, relationships, credibility, and legacy. Anthropology talks about a series of events in human (social) groups and the changes that occur which can be inherited or substantially revised, reinterpreted, and taken as an "academic sample" as a legacy for generations in which anthropology is re-studied. With its various types, observing anthropology requires using various methodologies and approaches. At the end of this article, I discuss biblical anthropology that looks at the totality of humanity in the light of the Scriptures. Abstrak: Artikel ini memandang antropologi tentang bagaimana manusia memahami dan menilai seluk-beluk kehidupan, dan mengambil kesimpulan untuk dijadikan pegangan hidup dalam membentuk moral, spiritual, kenyamanan, kedamaian, relasi, kredibilitas, dan legasi. Antropologi berbicara tentang rentetan peristiwa dalam kelompok manusia (sosial) dan perubahan-perubahan yang terjadi yang dapat dijadikan warisan atau revisi secara substansial, reinterpretasi, dan pengambilan “sampel akademis” sebagai warisan bagi generasi di mana antropologi itu dipelajari kembali. Dengan beragam jenisnya, mengamati antropologi perlu menggunakan berbagai metodologi dan pendekatan. Di akhir artikel ini, saya membahas antropologi biblika yang melihat totalitas manusia dalam terang Kitab Suci.